Introduction of Basic Geometry Shapes for Children Aged 5-6 Years Through Fashion Ready to Wear - Alfarist, Salsabila Zahra; Ratuannisa, Tyar (Moda : The Fashion Journal, 2024)
Learning for children aged 5-6 years requires concrete media so that learning can be conveyed well and students can understand learning easily. Based on the results of observations found problems in learning math geometry, namely the lack of media that supports learning geometry in the material so that students mastery of the material is still not optimal. Therefore, the focus of this research is to create design innovations by applying printing and knitting techniques as visual and sensory media on ready-to-wear clothing products for children aged 5-6 years to prevent delays in knowledge of geometric shapes before entering further education. This research was conducted using the creation theory method of “three stage design process”. The design is also meant to promote children’s fashion as part of a trend that is now rare to find. In addition, this design will produce a product that is different from other clothing products, this research produces a design concept and modification of geometric motifs applied to printing and knitting techniques using fabric materials applied to basic products of ready-made children’s clothing that has aesthetic and modern values.